The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1534/genetics.107.082867
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping and The Genetic Basis of Heterosis in Maize and Rice

Abstract: Despite its importance to agriculture, the genetic basis of heterosis is still not well understood. The main competing hypotheses include dominance, overdominance, and epistasis. NC design III is an experimental design that has been used for estimating the average degree of dominance of quantitative trait loci (QTL) and also for studying heterosis. In this study, we first develop a multiple-interval mapping (MIM) model for design III that provides a platform to estimate the number, genomic positions, augmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
118
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 31 publications
10
118
1
4
Order By: Relevance
“…However, previous studies have shown that a conclusion on the genetic basis of heterosis depends on a statistical approach adopted by [8,16,17,36]. Therefore, the development and choice of appropriate methodology for NCIII design are critical.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, previous studies have shown that a conclusion on the genetic basis of heterosis depends on a statistical approach adopted by [8,16,17,36]. Therefore, the development and choice of appropriate methodology for NCIII design are critical.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development and choice of appropriate methodology for NCIII design are critical. In Stuber et al [19] and Xiao et al [22], the separate analysis on each backcross population actually estimated d*+a* or d*−a* [11,14,16]. To overcome this issue, Cockerham and Zeng [11] separated the additive and dominance effects in their combined analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations